Lessons Learned About the Education Needs of Kidney Transplant Recipients: A Mixed-Method Study - Michelle L. Gabriel; Lucy Chen; Sharon Lee; Jenny Accettura; Emily E. Campbell; Melanie Dissanayake; Teresa J. Valenzano-Hacker; Michelle Nash; Lindita Rapi; Niki Dacouris; Weiqiu Yuan; Tiffany Thai (Canadian Journal of Kidney Health and Disease)
Background: Much of the literature on kidney transplant education focuses on educating recipients prior to transplant or in the early postoperative period. It is unknown whether the information provided is meaningful to patients or whether the importance of education topics changes with time. Objective: We sought to identify the learning needs of patients post-kidney transplant. Design: Our multidisciplinary team conducted a mixed-method study to better understand the learning needs of patients; what is important to them in the early postoperative period and a year after transplant. Setting: One urban academic hospital performing kidney transplant in Ontario, Canada. Data were collected between September 2019 and March 2021, including during the COVID-19 pandemic. Participants: A convenience sample of 20 participants in the post-kidney transplant clinic. Participants’ mean age was 56 (SD ± 11) with 75% of participants male gender. Methods: Twenty kidney transplant patients were recruited between 3 and 6 months post-transplant. Participants completed an initial demographic questionnaire. They completed the Learning Needs Inventory (LNI) and a one-on-one semi-structured interview at 2 time points: 3 to 6 months post-transplant and 12 to 18 months post-transplant. Results: Patient interviews revealed that their access to a trustworthy health care team, support system, and reported challenges post-transplant shaped their ability to engage in learning. Patients shared that each aspect influences when and what topics were important to them, which allowed patients to obtain personalized education. A multidisciplinary team extending beyond physicians and nurses to include professionals such as pharmacists, dietitians, and social workers can best address patient-specific education needs post-transplant was highlighted in patients’ comments. Patients revealed that their support system helps to develop self-reliance and support their transition after transplant to allow them to recover and manage challenges after transplant. Support systems varied from family, friends, colleagues and included social media and community organizations were helpful. Our study identified 3 realms of challenges post-transplant including: emotional, physical, and financial. Quantitative data showed significant findings on the level of importance regarding the use of alcohol, demonstrating a shift in median rating of “not important at all” to “not very important” ( P = .016). A significant effect ( P = .031) shifting the median rating of post-transplant dental care from of “a little important” to “very important.” Limitations: The small convenience sample with only English-speaking patients used in this study may have affected our ability for generalizable results. Part of this study was completed during the COVID-19 pandemic, which may have led to individual responses to vary, as priorities may have been different during the pandemic. Conclusion: Only 2 topics (dental care and use of alcohol) shifted in importance. Most education topics (ie, rejection, infection) covered in 3 to 6 months post-transplant continued to be important for those that have had their transplant for more than a year suggesting the need for ongoing education post-transplant. Multidisciplinary care teams play an important role in providing personalized education to patients and help to address emotional, physical, and financial challenges after transplant. This study showed the importance of social media and community organizations in patients’ education offering an additional avenue of support and to hear others, lived experiences. Trial registration: Not registered.